The Impact of Comprehensive Planning on Financial Performance - Wood, D. Robley; LaForge, R. Lawrence (Academy of Management Journal, 1979)
The relationship between formal planning procedures and financial performance was examined for a sample of large U.S. banks. It was found that the sample banks that engaged in comprehensive long range planning significantly outperformed those that had no formal planning system. They also outperformed a randomly selected control group.